Algorithm for the reconstruction of the parotid region: a single institution experience - Chun-Bo Dou; Si-Rui Ma; Shi-Long Zhang; Heng Su; Zi-Li Yu; Jun Jia (BMC, 2024)
Abstract Objective This study aims to discuss the characteristics and treatment methods of malignant tumors in the parotid region, as well as the therapeutic effects of immediate free flap reconstruction of soft tissue for postoperative defects. Materials and methods A retrospective review was conducted on 11 cases of soft tissue flap reconstruction for postoperative defects following the resection of malignant tumors in the parotid region. Statistical analysis was performed based on clinical data. Results Among the 11 cases of malignant tumors in the parotid region, there were 2 cases of secretory carcinoma (SC) of the salivary gland, 2 cases of squamous cell carcinoma (SCC), 2 cases of carcinosarcoma, 1 case of mucoepidermoid carcinoma (MEC), 1 case of epithelial-myoepithelial carcinoma (EMC), 1 case of salivary duct carcinoma (SDC), 1 case of basal cell carcinoma (BCC), and 1 case of osteosarcoma. Among these cases, 4 were initial diagnoses and 7 were recurrent tumors. The defect repairs involved: 8 cases with anterolateral thigh free flap (ALTF), 2 cases with pectoralis major muscle flaps, and 1 case with forearm flap. The size of the flaps ranged from approximately 1 cm × 3 cm to 7 cm × 15 cm. The recipient vessels included: 4 cases with the facial artery, 4 cases with the superior thyroid artery, and 1 case with the external carotid artery. The ratio of recipient vein anastomosis was: 57% for branches of the internal jugular vein, 29% for the facial vein, and 14% for the external jugular vein. Among the 8 cases that underwent neck lymph node dissection, one case showed lymph node metastasis on pathological examination. In the initial diagnosis cases, 2 cases received postoperative radiotherapy, and 1 case received 125I seed implantation therapeutic treatment after experiencing two recurrences. Postoperative follow-up revealed that 2 cases underwent reoperation due to local tumor recurrence, and there were 2 cases lost to follow-up. The survival outcomes after treatment included: one case of distant metastasis and one case of death from non-cancerous diseases. Conclusion Immediate soft tissue flap reconstruction is an important and valuable option to address postoperative defects in patients afflicted with malignant tumors in the parotid region.